Work Involvement, Work Attitude, Discipline and Commitment to Employee Productivity Office Regional Revenue Agency Labuhanbatu Regency - Irmayani Irmayani; Siti Lam'ah Nasution; Abd. Halim (Budapest International Research and Critics University, 2022)
This study aims to analyze work involvement, disciplined work attitude and commitment to employee productivity at the Regional Revenue Agency Office of Labuhanbatu Regency. This type of research is quantitative. In this study, the population was 90 employees of the Regional Revenue Agency Office of Labuhan Batu Regency. The sampling technique used is saturated sampling. Saturated sampling technique is a sampling technique when all members of the population are used as samples. Since the number of employees of the Labuhanbatu Regency Regional Revenue Agency is 90 people (less than 100 people), all employees are taken as objects of research. The analysis used is multiple linear regression. Observation, documentation and questionnaires using a Likert scale is a data collection technique used in this study. The multiple linear regression equation is as follows: Y=1,337+0,385X1+0,209X2 +0,256X3+0,733X4. Table 6 explains that the B value on work involvement (B1) is 0.385. The value of work attitude (B2) is 0.209. Discipline value (B3) is 0.256. The commitment value (B4) is 0.733, and the constant value (a) is 1.337. The description of the multiple linear regression equation shows that the variables of work involvement (X1), work attitude (X2), discipline (X3) and commitment (X4) have a positive direction coefficient on employee productivity. The value of Fcount is 27.571> Ftable 2.48 with a significance value of 0.000 <0.05. From these results, it can be concluded that work involvement (X1), work attitude (X2), discipline (X3) and commitment (X4) simultaneously have a positive and significant effect on employee productivity (Y). The value of R Square from the analysis of the coefficient of determination of 0.565 means that work productivity can be explained by the variables of work involvement (X1), work attitude (X2), discipline (X3) and commitment (X4) of 56.5%, while the remaining 43.5% can be explained by other variables not examined in this study